Strategi Adaptasi Mahasiswa Perantau terhadap Lingkungan Sosial Baru: Analisis Upaya Adaptasi dalam Menghadapi Tantangan Lingkungan Baru - fitri25, layyinah_ (Maliki Interdisciplinary Journal, 2026)
This article offers a thorough analysis of the different strategies used by non-local students to adjust to a new social setting in higher education. Drawing on a small-scale study that utilized in-depth interviews with four students from diverse regional backgrounds, the research investigates their early experiences when entering university life. These include cultural shock, learning unfamiliar social norms, and the process of forming new social connections. The study also identifies various challenges they face, such as language difficulties, contrasting communication styles, distancing from family, and increased academic pressure. Beyond discussing these challenges, the research emphasizes several elements that facilitate successful adaptation, including the quality of peer relationships, emotional and financial support from family, involvement in campus organizations or activities, and individual skills in handling stress and adjusting to cultural and environmental changes. The results suggest that adaptation is a dynamic process shaped by the interplay of both internal and external factors. The insights gained from this research are expected to assist universities and incoming students in recognizing the specific needs of non-local students and in creating more effective support strategies.